2018
DOI: 10.1016/j.drugalcdep.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Sex work, injection drug use, and abscesses: Associations in women, but not men

Abstract: Background Abscesses commonly occur among people who inject drugs (PWID). However, whether the risks are comparable between males and females, and the impact of sex work on abscess risk is unclear. The goal of this study was to examine the contemporary associations of gender and sex work with the risk of abscesses in PWID. Methods Combining data from two cross-sectional studies conducted in the Greater Boston Area with people at risk for HIV and hepatitis C virus (HCV), we used the following inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…These nonmodifiable risk factors, and limited public assistance for homes and suitable hygiene, highlight SSPs as plausible mechanism to reduce the number of WSI and associated complications. The increased risk of WSI in women is consistent with previous reports and could be secondary to smaller veins, injecting 'second' (i.e., after a different person) and injection by partners 33 . Interestingly, increasing age was associated with higher WSI risk but increased years injecting was not, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These nonmodifiable risk factors, and limited public assistance for homes and suitable hygiene, highlight SSPs as plausible mechanism to reduce the number of WSI and associated complications. The increased risk of WSI in women is consistent with previous reports and could be secondary to smaller veins, injecting 'second' (i.e., after a different person) and injection by partners 33 . Interestingly, increasing age was associated with higher WSI risk but increased years injecting was not, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…The increased risk of WSI in women is consistent with previous reports and could be secondary to smaller veins, injecting 'second' (i.e., after a different person) and injection by partners. 33 Interestingly, increasing age was associated with higher WSI risk but increased years injecting was not, which warrants further investigation. Importantly, cocaine injection was shown to be associated with higher incidence of WSI, consistent with prior literature, and even more critical in the fourth wave the of the US overdose crisis with coinjection of opioids and stimaulants.…”
Section: Discussionmentioning
confidence: 93%
“…However, the underlying mechanism by which trading sex influences HCV status among our sample is unclear. Importantly, although females in our study were more likely to trade sex than males, 56 including gender in the final model did not appreciably alter the association between trading sex and HCV status (data not shown), and gender was not associated significantly with HCV status among our sample at the bivariate or multivariable levels. Thus, although other work has shown that female PWID may be more at risk for HCV infection than males, 57,58 such an association was not reflected in our sample.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 62%
“…In rural northern New England, the introduction of fentanyl accelerated the opioid epidemic ( Somerville et al, 2017 ). Hepatitis C virus (HCV) rates ( Stopka et al, 2017 , 2019a , b ) and other comorbidities of drug injection, including infectious endocarditis and osteomyelitis ( Wurcel et al, 2016 , 2018 ), have similarly increased.…”
Section: Introductionmentioning
confidence: 99%